Analysis of Macroeconomics Effects on the Indonesian Sharia Stock Index - Anton Bawono; Imamul Mutaqin (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose- The purpose of this study was to analyze the response shown by the Indonesian sharia stock index (ISSI) against the shock that occurred in inflation, IDR / USD exchange rate, interest rate, money supply (JUB), world oil prices and world gold prices. Methods- This research is quantitative research using the VAR model as data analysis. The data have been obtained and analyzed using Eviews software tool version 9. Findings- These results indicate that the ISSI responded negatively and permanently against shock happens to inflation, ISSI responded negatively and permanently against the shock that occurred at the BI Rate, the ISSI responded positively and permanently to the shock that occurred in world oil prices, the ISSI responded positively and permanently to the shock that occurred at world gold prices. Research implications- Investors should pay attention to changes that might occur in inflation, interest rate, world oil prices and world gold prices because in the results of this study show that the stock index will respond at least 10 months ahead when inflation, BI Rate, world oil prices and world gold prices experience shock. The government is expected to maintain economic stability so investors remain interested in investing in the domestic stock market